Biomechanical musculoskeletal models of the cervical spine: A systematic literature review. (January 2020) - Alizadeh, Mina; Knapik, Gregory G.; Mageswaran, Prasath; Mendel, Ehud; Bourekas, Eric; Marras, William S.
Abstract: Background: As the work load has been shifting from heavy manufacturing to office work, neck disorders are increasing. However, most of the current cervical spine biomechanical models were created to simulate crash situations. Therefore, the biomechanics of cervical spine during daily living and occupational activities remain unknown. In this effort, cervical spine biomechanical models were systematically reviewed based upon different features including approach, biomechanical properties, and validation methods. Methods: The objective of this review was to systematically categorize cervical spine models and compare the underlying logic in order to identify voids in the literature. Findings: Twenty-two models met our selection criteria and revealed several trends: 1) The multi-body dynamics modeling approach, equipped for simulating impact situations were the most common technique; 2) Straight muscle lines of action, inverse dynamic/optimization muscle force calculation, Hill-type muscle model with only active component were typically used in the majority of neck models; and 3) Several models have attempted to validate their results by comparing their approach with previous studies, but mostly were unable to provide task-specific validation. Interpretation: EMG-driven dynamic model for simulating occupational activities, with accurate muscle geometry and force representation, and person- or task-specific validation of the model would be necessary to improve model fidelity. Highlights: Work related cervical spine injury is increasing due to modern sedentary work style. Cervical spine biomechanics during occupational activities is unknown due to computational modeling limitations. This review categorized cervical spine computational models and their modeling approaches for future development. Most of the models are capable of impact or quasi-static simulations rather than dynamic simulations. Inaccurate muscle structure and function modeling, enables current cervical spine models to predict spinal loading.